2011
DOI: 10.1111/j.1469-7580.2011.01344.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional anatomy of the cheetah (Acinonyx jubatus) forelimb

Abstract: Despite the cheetah being the fastest living land mammal, we know remarkably little about how it attains such high top speeds (29 m s )1 ). Here we aim to describe and quantify the musculoskeletal anatomy of the cheetah forelimb and compare it to the racing greyhound, an animal of similar mass, but which can only attain a top speed of 17 m s. Measurements were made of muscle mass, fascicle length and moment arms, enabling calculations of muscle volume, physiological cross-sectional area (PCSA), and estimates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
121
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(132 citation statements)
references
References 40 publications
8
121
2
1
Order By: Relevance
“…Across the whole dataset, maximum stride frequencies of 3.9Hz were used by both species; a maximum that far exceeds that used by other fast quadrupeds (Heglund and Taylor, 1988;Witte et al, 2006) and that previously observed for the cheetah (Hildebrand, 1961). For both species, a linear increase in stride length with speed was observed, and the cheetah used longer stride lengths than the greyhound, which can be explained by the cheetah's slightly longer limbs and back (Hudson et al, 2011a;Hudson et al, 2011b). During a gallop, the greyhound therefore appears to only increase its stride length; however, the cheetah uses a combination of increased stride frequency and stride length to achieve higher speeds.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Across the whole dataset, maximum stride frequencies of 3.9Hz were used by both species; a maximum that far exceeds that used by other fast quadrupeds (Heglund and Taylor, 1988;Witte et al, 2006) and that previously observed for the cheetah (Hildebrand, 1961). For both species, a linear increase in stride length with speed was observed, and the cheetah used longer stride lengths than the greyhound, which can be explained by the cheetah's slightly longer limbs and back (Hudson et al, 2011a;Hudson et al, 2011b). During a gallop, the greyhound therefore appears to only increase its stride length; however, the cheetah uses a combination of increased stride frequency and stride length to achieve higher speeds.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, the fastest canid, the racing greyhound (Canis familiaris L.), has a top speed of just 17ms -1 (Jayes and Alexander, 1982;Usherwood and Wilson, 2005), despite the two animals being of a similar mass and gross morphology. Anatomical studies (Hudson et al, 2011a;Hudson et al, 2011b) have presented no clear reason as to why there is such a large difference in their top speeds, and there is no clear consensus in the literature as to what fundamentally limits the maximum running speed of a quadruped. Here, we studied the kinematics and kinetics of galloping in the cheetah and racing greyhound to investigate how the cheetah attains faster speeds than the greyhound, and to explore some of the theorised limits to maximum running speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suspensory ligament, SDF and DDF muscles are all active during stance and are thought to support body weight [12].…”
Section: Discussionmentioning
confidence: 99%
“…Many biomechanical factors falling outside the scope of this study (each contributing to a different degree and related to species) could potentially affect power output and are worth mentioning. These include the mass of the animal, being quadrupedal or bipedal, lever arm angles and length of the limbs (affecting stride length), muscle and tendon lengths, and the ability to store elastic energy, to name but a few (Alexander, 2006;Hudson et al, 2011a;Hudson et al, 2011b).…”
Section: Comparing the Contractile Properties Of Human Single Fibres mentioning
confidence: 99%